PERAN BAWASLU DALAM PENGAWASAN PEMILU: STUDI KASUS PENYELENGGARAAN PILKADA SERENTAK DI KOTA DEPOK TAHUN 2020 - Rendi Muhammad, (2022)
In a democratic country, the role of public participation is absolutely necessary in order to exercise control over the current government. In a democratic country there is also a rule that true government comes from the people, by the people and for the people. As a consequence of this, citizens must choose their representatives who must sit in the seat of government. Furthermore, the community must also take part in participating. In this paper, the authors highlight how the efforts made by Bawaslu to boost participation from the community in the city of Depok. In addition, the author sees that the 2020 regional elections in Depok were carried out within the framework of a pandemic, and Depok City is a city with a fairly high spread of covid when compared to other cities in Bodetabek (884 cases) (Kompas.com, 2020) apart from Meanwhile, the first case of Covid was also found in Depok City. Therefore, the author considers the city of Depok to be quite an interesting context in terms of how Bawaslu attempts to suppress community participation. Departing from that, the author in this paper wants to try to describe what efforts have been made by the Depok City Bawaslu to boost the participation rate from the community. This paper is a qualitative research with a case study method, where the author wants to get a complex picture of how community participation works in the city of Depok, with the problems of the pandemic in the city of Depok. The authors use primary data and secondary data in this thesis. The primary data writer interviewed Dede Slamet Permana as a representative of the Depok City Bawaslu